Serum antineutrophil cytoplasmic antibody positivity at the time of renal biopsy is associated with disease activity of lupus nephritis - Jing Zhang; Ruoshan Lian; Yi Chen; Jianxin Wan (Renal Failure)
Objective To investigate the correlations between serum antineutrophil cytoplasmic antibody (ANCA) and clinicopathological features, induction treatment response, and prognosis of lupus nephritis (LN) patients.Methods In this retrospective study, biopsy-proven LN patients from October 2010 to September 2020 were tested for serum ANCA by indirect immunofluorescence and ELISA and were divided into ANCA-positive group and ANCA-negative group. The clinicopathological data of the two groups were analyzed and compared.Results Thirty-five of 115 patients (30.43%) were seropositive for ANCA. ANCA-positive patients had significantly higher systemic lupus erythematosus activity index and activity index scores, higher 24-h urinary protein, and lower complement three levels (p = 0.001, 0.028, 0.023, 0.009, respectively). The incidences of oral ulcers, thrombocytopenia, and leukocyturia, and the positive rates of anti-dsDNA antibody and anti-histone antibody were significantly higher in ANCA-positive group (p = 0.006, 0.019, 0.012, 0.001, 0.019, respectively). Class IV LN and fibrinoid necrosis/karyorrhexis were significantly more common in the ANCA-positive group (p = 0.027, 0.002). There was no significant difference in the total remission rate of ANCA-positive patients receiving cyclophosphamide and mycophenolate mofetil as induction therapies (83.33% vs. 66.67%, p > 0.05), while patients receiving cyclophosphamide as induction therapy had a higher total remission rate than those receiving other immunosuppressants (83.33% vs. 20%, p = 0.028).Conclusions LN patients with ANCA seropositivity at renal biopsy have a significantly higher disease activity, and their pathological manifestations are predominantly proliferative LN. These patients require a more active immunosuppressive therapy with cyclophosphamide or mycophenolate mofetil to improve their remission rate.